Kinetic study of multiphase reactions under microwave irradiation: A mini-review - Adavi, Kazem; Amini, Ahmadreza; Latifi, Mohammad; Shabanian, Jaber; Chaouki, Jamal (Frontiers in Chemical Engineering, 2022)
Microwave (MW) heating is rapid, selective, and volumetric, and it is a compelling non-conventional heating approach for driving chemical reactions. The effect of MW irradiation on the kinetics of thermal/catalytic reactions is still under debate. A group of researchers reported that the effect of MW heating on reaction kinetics is highlighted through the non-thermal effects of MWs on kinetic parameters and reaction mechanisms in addition to the thermal effect. However, another group attributed the observations to the thermal effect only. In the present work, we summarized and critically synthesized available information in the literature on the subject. It can be concluded that MW heating has solely the thermal effect on gas-solid reactions, and the variations of kinetic parameters are related to the direct and indirect impacts of that. Temperature measurement limitations, physical structure variation, and non-uniform temperature distribution are the primary sources of the discrepancy in previous studies. In ionic liquid-solid reactions, the presence of electromagnetic fields can affect the movement of ions/polar molecules which can be considered a non-thermal effect of MWs. However, the effect of MW absorption by solid/catalyst, and the formation of hot spots must be taken into account to avoid potential discrepancy. Therefore, further theoretical/experimental studies are required to clarify the effect of MWs on liquid-solid reactions. In addition, developing reliable temperature measurement methods and isothermal reaction domain are required for an accurate kinetic study during MW irradiation.